Evaluation of the Lowland Rice Sustainability Based on the Dimensions of Biological Control in Besur Village, Lamongan District - Aminudin Afandhi; Wilda Al Aluf; Budi Prasetya (Program Pascasarjana Universitas Brawijaya, 2019)
The biological control strategy in Besur Village of Lamongan District aims to increase the diversity of macroorganism natural enemies, the application of biological pesticides and to increase the diversity of microorganism biological technology. Excessive application of chemical pesticides inhibits the sustainability of lowland rice. This study aims to evaluate the sustainability of lowland rice based on biological control dimensions using the Multidimensional Scaling (MDS) method. The results of the MDS analysis showed that lowland rice farming is sufficiently sustainable with an diversity of macroorganism natural enemies by 1.96; the application of biological pesticides by 3.99 and the diversity of microorganism biological technology by 2.00. The application of biological pesticides plays a very important role in the sustainability of lowland rice in Besur Village of Lamongan district. It is recommended to improve the introduction of predators, parasitoid and insect pathogens to support the sustainability of lowland rice.Keywords: biological control, Besur, lowland rice, sustainability